Antistatic quick-drying chinlon multilayer composite fabric and preparation method thereof
By adopting a multi-layer composite structure of modified graphene, carbon bead layer and moisture absorption layer in nylon fabric, the problems of poor antistatic properties, poor fast drying performance and low mechanical strength of nylon fabric are solved, and efficient resistance is achieved Static, quick drying and antibacterial effects.
Patent Information
- Application Number
- CN202411478641.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing nylon fabrics have poor performance in antistatic and fast drying properties, and are not highly mechanically strong, resulting in static electricity generation, uncomfortable wearing and safety hazards, and insufficient moisture-absorbing and sweating performance.
Using a multi-layer composite structure of modified graphene, carbon bead layer and hygroscopic layer, modified graphene is prepared from bio-based nylon and modified graphene, and the carbon bead layer is prepared from carbon powder, phenolic resin, nanosilver and surfactant. The moisture absorbing layer is prepared by immersing the hygroscopic agent by bio-based nylon, and an anti-static fast-drying nylon multi-layer composite fabric is made by composite textile technology.
It improves the antistatic resistance and mechanical properties of the fabric, enhances the moisture absorption and quick-drying effect and antibacterial and mildew resistance, and improves the overall comfort and use value.
Smart Images

Figure CN119408275A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile fabrics, and in particular to an antistatic quick-drying nylon multi-layer composite fabric and a preparation method thereof. Background Art
[0002] With the development of the times, people have higher and higher requirements for fabrics, and developing fabrics that can meet consumer needs plays an increasingly important role in fabric production. Waterproof and breathable functional clothing can block the damage of bad weather and prevent rain and snow from penetrating, while also timely expelling sweat and moisture generated by exercise, thereby regulating the human microenvironment and providing good comfort for the human body, so that the protective function and comfort of clothing fabrics are unified;
[0003] The existing single-layer textile fabrics can no longer meet people's daily needs, especially in terms of anti-static and quick-drying performance. Single-layer fabrics cannot effectively resist static electricity. In addition, because fabrics are prone to breed a large number of bacteria or microorganisms after long-term use, it will affect its practicality and safety. Therefore, multi-layer composite fabrics have gradually received widespread attention.
[0004] Although traditional nylon fabrics have certain wear resistance and elasticity, they perform poorly in terms of anti-static and quick-drying properties. The generation of static electricity not only causes discomfort in wearing, but may also cause safety hazards such as spark discharge. At the same time, traditional nylon fabrics also have defects in moisture absorption and perspiration, making it difficult to meet the needs of quick drying.
[0005] In the prior art, the PA56 short fibers used in large quantities have a large specific resistance and serious electrostatic phenomena. Static charges often accumulate on the fiber surface and are not easy to dissipate. The electrostatic phenomenon in the fiber processing process will cause problems such as difficulty in the combing process, unclear yarn separation, and accumulation of flying flowers and dust. The patent with publication number CN114737271A mixes PA56 with graphene to produce graphene nylon fiber to improve the antistatic durability of graphene nylon fiber. However, the breaking strength of nylon filaments and yarns treated with graphene is significantly reduced, and the use value will also be greatly affected.
[0006] Therefore, the antistatic quick-drying nylon multi-layer composite fabric and related technologies still need to be further improved. Summary of the invention
[0007] In view of the deficiencies in the above-mentioned prior art, the purpose of the present invention is to provide an antistatic quick-drying nylon multi-layer composite fabric and a preparation method thereof, which solves the problems of poor antistatic performance and low mechanical strength of nylon fabrics in the prior art.
[0008] To achieve the above object, the present invention adopts the following technical solution:
[0009] On the one hand, the present invention provides an antistatic quick-drying nylon multi-layer composite fabric, which comprises, from the outside to the inside, a modified layer, a carbon bead layer, and a moisture absorption layer;
[0010] Wherein, the modified layer is prepared from bio-based nylon and modified graphene to obtain modified graphene nylon fabric, which is then blended into yarn and woven;
[0011] On the basis of this technical solution, it is further preferred that the carbon bead layer is prepared from carbon powder, phenolic resin, nanosilver and surfactant;
[0012] On the basis of this technical solution, it is further preferred that the moisture absorbing layer is made by soaking bio-based nylon in a moisture absorbing agent, blending it into yarn, and weaving it.
[0013] On the basis of this technical solution, further preferably, the desiccant comprises the following components in parts by weight: 80-100 parts of silicone oil, 12-20 parts of epoxy-terminated allyl polyether, 45-60 parts of DMF, 18-24 parts of n-dodecene, 0.8-1.6 parts of chloroplatinic acid and 30-42 parts of emulsifier.
[0014] On the basis of this technical solution, further preferably, the method for preparing the modified layer comprises the following steps:
[0015] Prepare modified graphene, add surfactant into graphene, ultrasonically disperse, filter, dry, then add polypropylene, ball mill and blend, granulate to obtain modified graphene;
[0016] Bio-based nylon is added, blended with modified graphene, melt-spun, and woven to obtain a modified layer.
[0017] On the basis of this technical solution, it is further preferred that the surfactant is cetylpyridinium chloride, and the molar ratio of the surfactant to graphene is 2.5-5%.
[0018] On the basis of this technical solution, further preferably, the molar ratio of the graphene to the polypropylene is 0.03-0.05:1.
[0019] On the basis of this technical solution, further preferably, the preparation method of the moisture absorbent comprises the following steps:
[0020] Weigh 80-100 parts of silicone oil, 12-20 parts of epoxy-terminated allyl polyether, 45-60 parts of DMF, and 18-24 parts of n-dodecene, add them into the reaction, mix and stir, and heat to 75-80°C;
[0021] Then add 0.8-1.6 parts of chloroplatinic acid, keep the temperature to react for 1-2 hours, cool down, distill, add 30-42 parts of emulsifier, mix well, add acid to adjust the pH to 7, and obtain a hygroscopic agent.
[0022] On the basis of this technical solution, further preferably, the carbon bead layer, the preparation method comprises the following steps:
[0023] Mix the carbon powder and phenolic resin, heat and stir to obtain a mixture.
[0024] The surfactant and the nano silver are then mixed to obtain a second mixture, and the first mixture and the second mixture are mixed to obtain a carbon bead layer by heating and stirring.
[0025] On the basis of this technical solution, further preferably, the molar ratio of the carbon powder to the phenolic resin is 1.5-2:1, and the molar ratio of the surfactant to the nanosilver is 0.9-1:1.
[0026] On the basis of this technical solution, it is further preferred that the immersion time of the bio-based nylon in the desiccant is 3-5 hours and the immersion temperature is 30-40°C.
[0027] On the other hand, the present invention also provides a method for preparing the antistatic quick-drying nylon multi-layer composite fabric, the preparation method comprising:
[0028] The modified layer, the carbon bead layer and the moisture-absorbing layer are compositely woven to obtain an antistatic quick-drying nylon multi-layer composite fabric.
[0029] The antistatic quick-drying nylon multi-layer composite fabric and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:
[0030] (1) The present invention uses modified graphene to form hydrogen bonds with groups of polypropylene through surface groups, thereby improving the crystallinity of polypropylene, thereby improving the mechanical properties of polypropylene / modified graphene fibers. When polypropylene / modified graphene fibers are used to modify existing bio-based nylon, the antistatic resistance is improved while maintaining a relatively high mechanical strength, thereby effectively solving the problem of reduced performance due to reduced breaking strength caused by improved antistatic properties.
[0031] (2) The present invention also effectively designs a hygroscopic layer, which is prepared from silicone oil, epoxy-terminated allyl polyether and dodecene, and then emulsified with an emulsifier, has good hygroscopicity, effectively penetrates the inside of fabrics and yarns, and improves the quick-drying effect;
[0032] (3) The present invention also designs a carbon bead layer, and utilizes the compound of carbon powder, phenolic resin and surfactant to obtain carbon beads with good stability, thereby enhancing the antibacterial, anti-mildew and anti-toxic effects of the multi-layer composite fabric, and improving the overall comfort of the composite fabric. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 This is a structural diagram of the antistatic quick-drying nylon multi-layer composite fabric shown in the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The invention provides an antistatic quick-drying nylon multi-layer composite fabric and a preparation method thereof, comprising a modified layer, a carbon bead layer and a moisture absorption layer; wherein the modified layer is prepared from bio-based nylon and modified graphene to obtain a modified graphene nylon fabric, which is then blended into yarn and woven; the carbon bead layer is prepared from carbon powder, phenolic resin, nano silver and a surfactant; the moisture absorption layer is prepared from bio-based nylon soaked in a moisture absorbent, blended into yarn and woven, thereby solving the problems of poor antistatic performance and low mechanical strength of nylon fabrics in the prior art.
[0037] Example 1
[0038] An antistatic quick-drying nylon multi-layer composite fabric, such as Figure 1 As shown, it includes: a modified layer, a carbon bead layer, a moisture absorbing layer,
[0039] The modified layer is prepared from bio-based nylon and modified graphene to obtain modified graphene nylon fabric, which is then blended into yarn and woven;
[0040] Specifically, the carbon bead layer is prepared from carbon powder, phenolic resin, nano silver and surfactant;
[0041] Specifically, the moisture absorbing layer is formed by soaking bio-based nylon in a moisture absorbing agent, blending the bio-based nylon into yarn, and weaving the yarn.
[0042] Specifically, the moisture absorbent includes the following ingredients: 80 g silicone oil, 12 g epoxy-terminated allyl polyether, 45 g DMF, 18 g n-dodecene, 0.8 g chloroplatinic acid and 30 g emulsifier.
[0043] Specifically, the method for preparing the modified layer comprises the following steps:
[0044] Prepare modified graphene, add surfactant into graphene, ultrasonically disperse, filter, dry, then add polypropylene, ball mill and blend, granulate to obtain modified graphene;
[0045] Bio-based nylon is added, blended with modified graphene, melt-spun, and woven to obtain a modified layer.
[0046] Specifically, the surfactant is cetylpyridinium chloride, and the molar ratio of the surfactant to graphene is 2.5%.
[0047] Specifically, the molar ratio of graphene to polypropylene is 0.03:1.
[0048] Specifically, the preparation method of the moisture absorbent comprises the following steps:
[0049] Weigh 80g silicone oil, 12g epoxy-terminated allyl polyether, 45g DMF, and 18g n-dodecene, add them into the reaction, mix well, and heat to 75°C;
[0050] Then add 0.8g of chloroplatinic acid, keep the temperature for reaction for 1h, cool down, distill, add 30g of emulsifier, mix well, add acid to adjust the pH to 7, and obtain a hygroscopic agent.
[0051] Specifically, the emulsifier is AEO-7.
[0052] Specifically, the carbon bead layer, the preparation method comprises the following steps:
[0053] Mix the carbon powder and phenolic resin, heat and stir to obtain a mixture.
[0054] The surfactant and the nano silver are then mixed to obtain a second mixture, and the first mixture and the second mixture are mixed to obtain a carbon bead layer by heating and stirring.
[0055] Specifically, the molar ratio of the carbon powder to the phenolic resin is 1.5:1, and the molar ratio of the surfactant to the nanosilver is 0.9:1.
[0056] Specifically, the bio-based nylon is immersed in the moisture absorbent for 3 hours at a temperature of 30°C.
[0057] The preparation method of the antistatic quick-drying nylon multi-layer composite fabric comprises:
[0058] The modified layer, the carbon bead layer and the moisture-absorbing layer are compositely woven to obtain an antistatic quick-drying nylon multi-layer composite fabric.
[0059] Example 2
[0060] An antistatic quick-drying nylon multi-layer composite fabric, comprising: a modified layer, a carbon bead layer, and a moisture absorption layer.
[0061] The modified layer is prepared from bio-based nylon and modified graphene to obtain modified graphene nylon fabric, which is then blended into yarn and woven;
[0062] Specifically, the carbon bead layer is prepared from carbon powder, phenolic resin, nano silver and surfactant;
[0063] Specifically, the moisture absorbing layer is formed by soaking bio-based nylon in a moisture absorbing agent, blending the bio-based nylon into yarn, and weaving the yarn.
[0064] Specifically, the desiccant includes the following components in parts by weight: 100 g of silicone oil, 20 g of epoxy-terminated allyl polyether, 60 g of DMF, 24 g of n-dodecene, 1.6 g of chloroplatinic acid and 42 g of emulsifier.
[0065] Specifically, the method for preparing the modified layer comprises the following steps:
[0066] Prepare modified graphene, add surfactant into graphene, ultrasonically disperse, filter, dry, then add polypropylene, ball mill and blend, granulate to obtain modified graphene;
[0067] Bio-based nylon is added, blended with modified graphene, melt-spun, and woven to obtain a modified layer.
[0068] Specifically, the surfactant is cetylpyridinium chloride, and the molar ratio of the surfactant to graphene is 5%.
[0069] Specifically, the molar ratio of graphene to polypropylene is 0.05:1.
[0070] Specifically, the preparation method of the moisture absorbent comprises the following steps:
[0071] Weigh 100g silicone oil, 20g epoxy-terminated allyl polyether, 60g DMF, and 24g n-dodecene, add them into the reaction, mix well, and heat to 80°C;
[0072] Then add 1.6 g of chloroplatinic acid, keep the temperature for reaction for 2 hours, cool down, distill, add 42 g of emulsifier, mix well, add acid to adjust the pH to 7, and obtain a hygroscopic agent.
[0073] Specifically, the emulsifier is AEO-7.
[0074] Specifically, the carbon bead layer, the preparation method comprises the following steps:
[0075] Mix the carbon powder and phenolic resin, heat and stir to obtain a mixture.
[0076] The surfactant and the nano silver are then mixed to obtain a second mixture, and the first mixture and the second mixture are mixed to obtain a carbon bead layer by heating and stirring.
[0077] Specifically, the molar ratio of the carbon powder to the phenolic resin is 2:1, and the molar ratio of the surfactant to the nanosilver is 1:1.
[0078] Specifically, the bio-based nylon is immersed in the moisture absorbent for 5 hours at a temperature of 40°C.
[0079] The preparation method of the antistatic quick-drying nylon multi-layer composite fabric described above comprises:
[0080] The modified layer, the carbon bead layer and the moisture-absorbing layer are compositely woven to obtain an antistatic quick-drying nylon multi-layer composite fabric.
[0081] Example 3
[0082] An antistatic quick-drying nylon multi-layer composite fabric, comprising: a modified layer, a carbon bead layer, and a moisture absorption layer.
[0083] The modified layer is prepared from bio-based nylon and modified graphene to obtain modified graphene nylon fabric, which is then blended into yarn and woven;
[0084] Specifically, the carbon bead layer is prepared from carbon powder, phenolic resin, nano silver and surfactant;
[0085] Specifically, the moisture absorbing layer is formed by soaking bio-based nylon in a moisture absorbing agent, blending the bio-based nylon into yarn, and weaving the yarn.
[0086] Specifically, the desiccant comprises the following components in parts by weight: 90 g of silicone oil, 18 g of epoxy-terminated allyl polyether, 55 g of DMF, 20 g of n-dodecene, 1.2 g of chloroplatinic acid and 38 g of emulsifier.
[0087] Specifically, the method for preparing the modified layer comprises the following steps:
[0088] Prepare modified graphene, add surfactant into graphene, ultrasonically disperse, filter, dry, then add polypropylene, ball mill and blend, granulate to obtain modified graphene;
[0089] Bio-based nylon is added, blended with modified graphene, melt-spun, and woven to obtain a modified layer.
[0090] Specifically, the surfactant is cetylpyridinium chloride, and the molar ratio of the surfactant to graphene is 4%.
[0091] Specifically, the molar ratio of graphene to polypropylene is 0.04:1.
[0092] Specifically, the preparation method of the moisture absorbent comprises the following steps:
[0093] Weigh 90g silicone oil, 18g epoxy-terminated allyl polyether, 55g DMF, and 20g n-dodecene, add them into the reaction, mix well, and heat to 78°C;
[0094] Then add 1.2g of chloroplatinic acid, keep the temperature for reaction for 1.5h, cool down, distill, add 38g of emulsifier, mix well, add acid to adjust the pH to 7, and obtain a hygroscopic agent.
[0095] Specifically, the emulsifier is AEO-7.
[0096] Specifically, the carbon bead layer, the preparation method comprises the following steps:
[0097] Mix the carbon powder and phenolic resin, heat and stir to obtain a mixture.
[0098] The surfactant and the nano silver are then mixed to obtain a second mixture, and the first mixture and the second mixture are mixed to obtain a carbon bead layer by heating and stirring.
[0099] Specifically, the molar ratio of the carbon powder to the phenolic resin is 1.8:1, and the molar ratio of the surfactant to the nanosilver is 0.95:1.
[0100] Specifically, the bio-based nylon is immersed in the moisture absorbent for 4 hours at a temperature of 35°C.
[0101] The preparation method of the antistatic quick-drying nylon multi-layer composite fabric described above comprises:
[0102] The modified layer, the carbon bead layer and the moisture-absorbing layer are compositely woven to obtain an antistatic quick-drying nylon multi-layer composite fabric.
[0103] Example 4
[0104] An antistatic quick-drying nylon multi-layer composite fabric, comprising: a modified layer, a carbon bead layer, and a moisture absorption layer.
[0105] The modified layer is prepared from bio-based nylon and modified graphene to obtain modified graphene nylon fabric, which is then blended into yarn and woven;
[0106] Specifically, the carbon bead layer is prepared from carbon powder, phenolic resin, nano silver and surfactant;
[0107] Specifically, the moisture absorbing layer is formed by soaking bio-based nylon in a moisture absorbing agent, blending the bio-based nylon into yarn, and weaving the yarn.
[0108] Specifically, the desiccant comprises the following components in parts by weight: 80 g of silicone oil, 12 g of epoxy-terminated allyl polyether, 45 g of DMF, 18 g of n-dodecene, 0.8 g of chloroplatinic acid and 30 g of emulsifier.
[0109] Specifically, the method for preparing the modified layer comprises the following steps:
[0110] Prepare modified graphene, add surfactant into graphene, ultrasonically disperse, filter, dry, then add polypropylene, ball mill and blend, granulate to obtain modified graphene;
[0111] Bio-based nylon is added, blended with modified graphene, melt-spun, and woven to obtain a modified layer.
[0112] Specifically, the surfactant is cetylpyridinium chloride, and the molar ratio of the surfactant to graphene is 3%.
[0113] Specifically, the molar ratio of graphene to polypropylene is 0.04:1.
[0114] Specifically, the preparation method of the moisture absorbent comprises the following steps:
[0115] Weigh 80g silicone oil, 12g epoxy-terminated allyl polyether, 45g DMF, and 18g n-dodecene, add them into the reaction, mix well, and heat to 75°C;
[0116] Then add 0.8g of chloroplatinic acid, keep the temperature for reaction for 1h, cool down, distill, add 30g of emulsifier, mix well, add acid to adjust the pH to 7, and obtain a hygroscopic agent.
[0117] Specifically, the emulsifier is AEO-9.
[0118] Specifically, the carbon bead layer, the preparation method comprises the following steps:
[0119] Mix the carbon powder and phenolic resin, heat and stir to obtain a mixture.
[0120] The surfactant and the nano silver are then mixed to obtain a second mixture, and the first mixture and the second mixture are mixed to obtain a carbon bead layer by heating and stirring.
[0121] Specifically, the molar ratio of the carbon powder to the phenolic resin is 1.5-2:1, and the molar ratio of the surfactant to the nanosilver is 0.9-1:1.
[0122] Specifically, the bio-based nylon is immersed in the moisture absorbent for 3-5 hours at a temperature of 30-40°C.
[0123] The preparation method of the antistatic quick-drying nylon multi-layer composite fabric described above comprises:
[0124] The modified layer, the carbon bead layer and the moisture-absorbing layer are compositely woven to obtain an antistatic quick-drying nylon multi-layer composite fabric.
[0125] Comparative Example 1
[0126] An antistatic nylon composite fabric, which differs from Example 1 in that no modified layer is provided.
[0127] Comparative Example 2
[0128] An antistatic nylon composite fabric, which differs from Example 2 in that no moisture absorption layer is provided.
[0129] Comparative Example 3
[0130] An antistatic nylon composite fabric, which differs from Example 3 in that no carbon bead layer is provided.
[0131] Comparative Example 4
[0132] An antistatic nylon composite fabric, which differs from Example 4 in that no modified layer is provided, but the outer part of the hygroscopic layer and the carbon bead layer is woven by blending existing bio-based nylon with graphene, blending into yarn.
[0133] Comparative Example 5
[0134] An antistatic nylon composite fabric, which differs from Example 1 in that the molar ratio of graphene to polypropylene is 0.2:1.
[0135] Comparative Example 6
[0136] An antistatic nylon composite fabric, which differs from Example 1 in that the molar ratio of the carbon powder to the phenolic resin is 3:1, and the molar ratio of the surfactant to the nanosilver is 0.5:1.
[0137] Performance testing
[0138] According to GB / T 12703 "Evaluation of electrostatic properties of textiles", the resistivity of the antistatic nylon composite fabrics prepared in all examples and controls was measured. The specifications of the fabrics in all examples and controls were 4cm×4cm, and the mechanical strength was measured according to the method of FZ / T01085-2009 "Test method for peeling strength of hot-melt adhesive interlining". In addition, the moisture absorption and quick-drying properties of all examples and controls were tested with reference to the test method of GB / T 21655.1-2008 "Evaluation of moisture absorption and quick-drying properties of textiles". Finally, the antibacterial property was tested with reference to GB / T21510-2008 "Test method for antibacterial properties of nano-inorganic materials".
[0139] Table 1 Performance test of antistatic nylon composite fabric
[0140]
[0141]
[0142] As can be seen from Table 1, the results of Example 1 and Comparative Examples 1, 4, and 5 show that the polypropylene / modified graphene fiber further modifies the existing bio-based nylon, effectively improving the antistatic resistance of the composite fabric. At the same time, the results of Comparative Examples 4 and 5 show that while the polypropylene / modified graphene fiber improves the antistatic performance, it also maintains a high mechanical strength as much as possible and has a better use value.
[0143] The results of Example 2 and Comparative Examples 2 and 6 show that the silicone oil, epoxy-terminated allyl polyether and dodecene are prepared and then emulsified with an emulsifier, and have good hygroscopicity, effectively penetrate the inside of fabrics and yarns, and improve the quick-drying effect.
[0144] The results of Example 3 and Comparative Example 3 show that the carbon beads obtained by compounding carbon powder with phenolic resin and surfactant have good stability, thereby enhancing the antibacterial properties of the multi-layer composite fabric.
[0145] In summary, the present invention provides an antistatic quick-drying nylon multi-layer composite fabric and a preparation method thereof, which has a composite structure of a modified layer, a moisture absorption layer and a carbon bead layer, thereby obtaining a composite fabric with excellent antistatic performance, quick-drying effect and antibacterial effect, while avoiding a significant reduction in mechanical properties and having good use value.
[0146] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An antistatic quick-drying nylon multi-layer composite fabric, characterized in that: From outside to inside, it includes: modified layer, carbon bead layer, and moisture absorption layer; Wherein, the modified layer is prepared from bio-based nylon and modified graphene to obtain modified graphene nylon fabric, which is then blended into yarn and woven; The carbon bead layer is prepared from carbon powder, phenolic resin, nano silver and surfactant; The moisture absorbing layer is formed by soaking bio-based nylon in moisture absorbing agent, blending into yarn and weaving.
2. The antistatic quick-drying nylon multi-layer composite fabric according to claim 1, characterized in that: The desiccant comprises the following components in parts by weight: 80-100 parts of silicone oil, 12-20 parts of epoxy-terminated allyl polyether, 45-60 parts of DMF, 18-24 parts of n-dodecene, 0.8-1.6 parts of chloroplatinic acid and 30-42 parts of emulsifier.
3. The antistatic quick-drying nylon multi-layer composite fabric according to claim 1, characterized in that: The method for preparing the modified layer comprises the following steps: Prepare modified graphene, add surfactant into graphene, ultrasonically disperse, filter, dry, then add polypropylene, ball mill and blend, granulate to obtain modified graphene; Bio-based nylon is added, blended with modified graphene, melt-spun, and woven to obtain a modified layer.
4. The antistatic quick-drying nylon multi-layer composite fabric according to claim 3, characterized in that: The surfactant is cetylpyridinium chloride, and the molar ratio of the surfactant to graphene is 2.5-5%.
5. The antistatic quick-drying nylon multi-layer composite fabric according to claim 3, characterized in that: The molar ratio of the graphene to the polypropylene is 0.03-0.05:
1.
6. The antistatic quick-drying nylon multi-layer composite fabric according to claim 2, characterized in that: The preparation method of the moisture absorbent comprises the following steps: Weigh 80-100 parts of silicone oil, 12-20 parts of epoxy-terminated allyl polyether, 45-60 parts of DMF, and 18-24 parts of n-dodecene, add them into the reaction, mix and stir, and heat to 75-80°C; Then add 0.8-1.6 parts of chloroplatinic acid, keep the temperature to react for 1-2 hours, cool down, distill, add 30-42 parts of emulsifier, mix well, add acid to adjust the pH to 7, and obtain a hygroscopic agent.
7. The antistatic quick-drying nylon multi-layer composite fabric according to claim 1, characterized in that: The carbon bead layer, the preparation method comprises the following steps: Mix the carbon powder and phenolic resin, heat and stir to obtain a mixture. The surfactant and the nano silver are then mixed to obtain a second mixture, and the first mixture and the second mixture are mixed to obtain a carbon bead layer by heating and stirring.
8. The antistatic quick-drying nylon multi-layer composite fabric according to claim 7, characterized in that: The molar ratio of the carbon powder to the phenolic resin is 1.5-2:1, and the molar ratio of the surfactant to the nanosilver is 0.9-1:
1.
9. The antistatic quick-drying nylon multi-layer composite fabric according to claim 1, characterized in that: The soaking time of the bio-based nylon soaking in the moisture absorbent is 3-5 hours, and the soaking temperature is 30-40°C.
10. The method for preparing the antistatic quick-drying nylon multi-layer composite fabric according to any one of claims 1 to 9, characterized in that: The preparation method comprises: The modified layer, the carbon bead layer and the moisture-absorbing layer are compositely woven to obtain an antistatic quick-drying nylon multi-layer composite fabric.
Citation Information
Patent Citations
Antistatic chinlon fabric treatment method
CN114737271A
Preparation method of graphene-chinlon nano-composite fibers
CN105862158A
Composite fabric for breathable protective clothing and breathable protective clothing
CN113897792A
Moisture absorption and sweat releasing finishing agent for cotton and preparation method thereof
CN115717335A
Method of producing a nonwoven textile comprising a barrier and an antistatic treatment
US20130115843A1
Cited By
Carbon material fiber bundling method
CN121272724A
A method of bundling carbon material fibers
CN121272724B